Ketahanan tiga klon jahe (Zingiber officinale Rosc.) terhadap penyakit layu bakteri (Ralstonia solanacearum) - Yulia Fista Fauzia; Suhartiningsih Dwi Nurcahyanti (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2020)
Ginger (Zingiber officinale Rosc.) Is one type of rhizome plant commonly used as a medicinal plant or spice. The rhizome is aromatic and has a distinctive odor used by the community to be used as spices, cooking ingredients and medicinal sources. So far the results of ginger production have not been able to meet people's consumption needs due to a decrease in ginger production at the main ginger development center (West Java). One of the main constraints of ginger cultivation is the attack of bacterial wilt disease caused by the bacterium R. solanacearum. One effort that can be done in tackling bacterial wilt in ginger plants is by using clones that are resistant to bacterial wilt disease of R. solanacearum. The experimental design was carried out using factorial Completely Randomized Design, using ginger clones and the application of R. solanacearum bacteria. This design consists of 6 treatments and 4 replications. Each replication unit consists of 4 plants, so the total number of plants used is 96 plants. The experimental results were analyzed using regression correlation analysis on the parameters of disease progression, while on plant growth parameters using variance analysis and if there were significant differences then continued with Duncan Multiple Range Test (DMRT) with a confidence level of 95%. The results showed red ginger clones including rather resistant criteria with a severity value of 25% while ginger empirical clones and elephant ginger clones were critically vulnerable with 75% severity values and 85.42%. Red ginger clones are more responsive to the infection of R. solanacearum bacteria so that the highest phenol content increases compared to other clones of 0.297 mg/ml, the phenol compounds that play a role in increasing plant resistance. In the variable growth of ginger emprit clone plants have a higher plant height and number of leaves compared to other clones, namely 43.83 cm and 15.44.